Analogies, Possibilities and Probabilities: Joel Marcus’s John the Baptist - Klawans, Jonathan (Journal for the study of the historical Jesus, 2021)
This essay dialogues with Joel Marcus’s volume on John the Baptist. After praising Marcus’s penchant for introducing helpful analogies, questions are raised regarding two of Marcus’s hypotheses. First, it is difficult to accept that the Baptist was ever associated with the Qumran sectarians; second, it is equally doubtful that the Baptist was a nuanced legal reformer. A third section probes additional matters regarding the Baptist and purity in ancient Judaism. The common denominator to many issues raised here is Marcus’s tendency to treat the possible as probable.